Preserving nature through people management: how can HRM contribute to environmental sustainability? - Capaul, Angela Nina (2019)
Companies as significant emissions contributors are required to apply a pro-environmental business approach when facing the challenges of global warming for compliance reasons and to exhibit a competitive advantage. HRM with its role in mobilizing employees could be ideally positioned to promote the tackling of environmental-related issues. This literature review, therefore, aims to answer the question of how HRM can contribute to the environmental sustainability of an organization. The results revealed several Green HRM practices, their effectiveness and measurement, the role of the HR department and the impact on organizational performance. Several shortfalls, practical implications, and future avenues are discussed.